Chaos and Control of Game Model Based on Heterogeneous Expectations in Electric Power Triopoly - Weizhuo Ji (Discrete Dynamics in Nature and Society)
A dynamic repeated game model has been established based on heterogeneous expectations in electric power triopoly. Theoretical analysis and numerical simulation show the complexity of this model; suppose that the producers make decisions with naive expectation and bounded rationality. The straight-line stabilization chaos control method was successfully applied to the dynamic repeated game model. The results have important practical value for the producers in the electric power oligopoly.